Gulf of Maine Harmful Algal Bloom in summer 2005 – Part 2: Coupled Bio-physical Numerical Modeling - He, Ruoying (J Geophys Res, 2008)
A coupled physical/biological modeling system was used to hindcast the 2005 Alexandrium fundyense bloom in the Gulf of Maine and investigate the relative importance of factors governing the bloom’s initiation and development. The coupled system consists of a state-of-the-art, free-surface primitive equation Regional Ocean Modeling System (ROMS) tailored for the Gulf of Maine (GOM) using a multi-nested configuration, and a population dynamics model for A. fundyense. The system was forced by realistic momentum and buoyancy fluxes, tides, river runoff, observed A. fundyense benthic cyst abundance, and climatological nutrient fields. Extensive comparisons were made between simulated (both physical and biological) fields and in-situ observations, revealing that the hindcast model is capable of reproducing the temporal evolution and spatial distribution of the 2005 bloom. Sensitivity experiments were then performed to distinguish the roles of three major factors hypothesized to contribute to the bloom: 1) the high abundance of cysts in western GOM sediments; 2) strong northeaster storms with prevailing downwelling-favorable winds; and 3) a large amount of fresh water input due to abundant rainfall and heavy snowmelt. Results suggested that the high abundance of cysts in western GOM was the primary factor of the 2005 bloom. Wind forcing was an important regulator, as episodic bursts of northeast winds caused onshore advection of offshore populations. These downwelling favorable winds accelerated the alongshore flow, resulting in transport of high cell concentrations into Massachusetts Bay. A large regional bloom would still have happened, however, even with normal or typical winds for that period. Anomalously high river runoff in 2005 resulted in stronger buoyant plumes/currents, which facilitated the transport of cell population to the western GOM. While affecting nearshore cell abundance in Massachusetts Bay, the buoyant plumes were confined near to the coast, and had limited impact on the gulf-wide bloom distribution.